Chiến lược quản lý đánh bắt thủy sản tối ưu tại Việt Nam trong điều kiện nóng lên toàn cầu - Nguyễn Hữu , Dũng; Đỗ Phương Yến , Linh; Ngô Thị Phương, Trang; Nguyễn Huyền , Mỹ; Ngô Thị Kim , Chi; Đồng Tố Hà , Phương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This paper investigates the optimal fishery management in Vietnam under climate change by comparing three scenarios. Scenario 1 maintains the current harvesting effort. Scenario 2 closes the sea for fishery biomass conservation. Scenario 3 pursues the maximum economic yield (MEY). The bioeconomic model is utilized, with the fishery yield function depending on the sea surface temperature affected by global warming rising at an annual rate of 0.010C, starting from 26.350C in the base year 2013. The secondary data for the period 2013–2020 was collected from the General Statistics Office and the World Bank Database for the model regression. The results show that if Vietnam continues the current harvesting effort (Scenario 1), the fishing intensity combined with global warming may lead to the collapse of the fishery in the long run. In contrast, if Vietnam bans fishing (Scenario 2), the stock may recover, but the industry makes no profit. The most feasible strategy is MEY (Scenario 3), where both the stock and profit are positive even under the impact of global warming. However, the unexpected consequence of MEY is the reduction of fish production and profit; thus, the implementation of such a policy requires integrating climate change mitigation policies. At present, an intermediate strategy such as establishing various conservation zones for fish recovery, jointly with ongoing harvesting in the other areas under the transferable quota system and climate change adaptation institution, can be a feasible solution to rebuild the fishery ecosystem and maintain economic value.